Factor VII and Fibrinogen Levels Examined by Age, Sex, and other Atherosclerotic Risk Factors in a Japanese Population - Ishikawa, Shizukiyo; Kario, Kazuomi; Nago, Naoki; Kayaba, Kazunori; Hiraoka, Jun; Matsuo, Hitoshi; Goto, Tadao; Miyamoto, Takeshi; Tsutsumi, Akizumi; Nakamura, Yoshikazu; Shimada, Kazuyuki; Inoue, Kazuo; Igarashi, Masahiro (Thrombosis and Haemostasis, 1997)
Factor VII coagulant activity (FVIIc) and fibrinogen (Fbg) levels have been investigated as cardiovascular risk factors. We studied these two factors with stratification for age, sex and blood pressure, and the relation with other atherosclerotic risk factors in a Japanese general population. The subjects were 3,139 Japanese (1,315 males and 1,824 females) aged 30 to 89 in 1992 and 1993. A linear increase with age was observed in the levels of Fbg in both men and women, but no differences were observed between men and women in each age group. A linear increase with age was also seen in the levels of FVIIc in women, but the levels of FVIIc in men were significantly higher for the age group 40-49 years than for any other age group. The levels of FVIIc in women were significantly higher than in men at age ≥60 years. As concerning the effect of alcohol intake status, Fbg had a tendency to decrease with alcohol intake. Fbg and FVIIc levels were associated with an increase in smoking status in men, but no association was seen in women in either Fbg or FVIIc. FVIIc was positively correlated with age, body mass index, total cholesterol, triglycerides and fasting insulin level. Fbg was positively correlated with age, systolic blood pressure, diastolic blood pressure, total cholesterol, LDL-cholesterol and triglycerides in women, but Fbg had few positive correlations with risk factors in men.A comparison with previous Western studies showed that the Fbg levels of our Japanese population were lower than those of the Caucasians studied, but the present FVIIc levels were nearly the same level or slightly higher than theirs. The association of Fbg and FVIIc and with other cardiovascular risk factors in Japanese was similar to those observed in Caucasians.